201T1 for Myocardial Imaging - Pohost, G. M. (Nuklearmedizin - NuclearMedicine, 1978)
201T1 is an agent which allows good quality myocardial imaging with the gamma-camera. Its distribution in the myocardium is related primarily to perfusion and myocardial cellular integrity. Redistribution into regions of decreased activity identifies ischemic myocardium whereas persistent reduction of regional activity occurs in areas of infarction. 201T1 imaging appears to provide a means of differentiating between myocardial ischemia and infarction and is therefore applicable to exercise stress testing as well as to the acute coronary situation.